1992
DOI: 10.1177/009102609202100105
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Leader Behavior on Subordinate Satisfaction in a Civil Service-Asian Context

Abstract: One of the greatest contributions of British Colonialism in the Asian Countries is the establishment of Civil Service Administration. While political, economic and cultural systems and values have changed over the years, the Civil Service Administration has been preserved intact in most of these countries. The continuity of most of these nations since the British Raj can be attributed very well to their Civil Service systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Beside its common use on American managers in the USA, the LBDQ instrument has also been applied successfully in Asia. The LBDQ was used in Singapore resulting in high reliabilities (Putti and Tong, 1992). Black and Porter (1991) used the LBDQ XII to compare the leadership behaviour of three samples of managers; American managers in the USA, American managers in Hong Kong and Hong Kong Chinese managers in Hong Kong and they found the reliability to be consistent at acceptable to moderately high levels for all of the samples.…”
Section: Methodsmentioning
confidence: 99%
“…Beside its common use on American managers in the USA, the LBDQ instrument has also been applied successfully in Asia. The LBDQ was used in Singapore resulting in high reliabilities (Putti and Tong, 1992). Black and Porter (1991) used the LBDQ XII to compare the leadership behaviour of three samples of managers; American managers in the USA, American managers in Hong Kong and Hong Kong Chinese managers in Hong Kong and they found the reliability to be consistent at acceptable to moderately high levels for all of the samples.…”
Section: Methodsmentioning
confidence: 99%
“…This theory has been successfully employed in a project facilitated by the first author running since 1997 comparing preferred leader behaviour across societal cultures. That decision was made in 1997 due to the project starting in China and the LBDQXII being one of the few having been employed in Chinese cultures, used in Hong Kong by Black and Porter (1991) and Selmer (1997), and in Singapore (Putti and Tong, 1992). Studies reported in Littrell (2013b) find the LBDQXII reliability to be consistent at acceptable to moderately high levels across cultures.…”
Section: Theories Selected For This Studymentioning
confidence: 99%
“…However, there is the occasional, albeit very limited, evidence that applying a non-culturally congruent leadership style can be preferred by local employees (see e.g. Putti and Tong, 1992;Selmer, 1996). However, studies examining the relationship between organizational outcomes and leadership style found that effective leaders had adapted to the local style (Ayman and Chemers, 1991;Gebert and Steinkamp, 1991;Yeh, 1995;Silverthorne and Wang, 2001).…”
Section: Conclusion and Limitationsmentioning
confidence: 99%